(untitled) (Economic studies journal, 2018)
The study aimed to confirm the basic role of vocational training. The study referred to the modern human resources’ plan which emerged within the goals of the third millennium،which called for increasing the proportion of graduates of technical vocational training institutions، keeping pace with current developments and future changes in mechanisms، techniques، and methods of production and operation. The study adopted Sudan case study to identify the reality of the curricula and methods of vocational training، and the extent of its openness to the leading experiences in the Islamic world and the Arab in this field It referred to the experience of the partnership agreement between Sudan and Turkey as a leading model in the field of vocational training. The study reached at number of results.The most important of which are as follows: The lack of realistic national strategies in the field of vocational training. Inadequate curricula، educational and training programs for development needs and local and external labor market requirements، the need to review the admission policies to encourage members of the community to vocational training programs. to develop its methods and use modern and sophisticated equipment، and techniques that are compatible with the local and external labor market. Providing the necessary funding by establishing an international Islamic fund to develop the technical vocational training system according a strategic plan.